Religious Moderation Practices in Islamic Religious Education in Multicultural Communities in Bali - Dewi Anggraeni; Annisa Oktaviani Abkha; Wafiq Rosalin Syifa Azizah; Sabita Lighoyati Kadza; Tsabita Millatina Taufiq; Dewi Ainia Mufiatun Nafisah (MKWK PAI Universitas Jambi, 2023)
This study aims to analyze religious moderation in a multicultural society in Bali through Islamic Religious Education at MAN 1 Jembrana. Islamic Education Institutions, through learning Islamic Religious Education, organize various educational activities that are inclusive and open to diversity. Qualitative methods were used for data collection through observation, interviews, and documentation techniques to provide descriptive analysis. Data analysis techniques were studied regarding qualitative research designs. This study concludes that the conception of religious moderation in learning Islamic Religious Education refers to respect for diversity, as practiced by the Prophet Muhammad during his reign in Medina. This conception is realized in practice: 1) Formation of Gantara, 2) Inter-religious dialogue, and 3) Preservation of traditions and cultural values ​​of the Balinese people. The practice of religious moderation applied by MAN 1 Jembrana can be a rule model in building a harmonious society amidst differences.